2009
DOI: 10.1348/000712608x329525
|View full text |Cite
|
Sign up to set email alerts
|

Men's preferences for women's profile waist‐to‐hip ratio, breast size, and ethnic group in Britain and South Africa

Abstract: One particular aspect of the literature on preferences for female body shapes has focused on the purported universality of preferences for a low waist-to-hip ratio (WHR), despite substantial evidence of cross-cultural variability in such preferences. In the present study, we examined the effects of manipulating women's profile WHR, breast size, and ethnicity on men's ratings of physical attractiveness and health. A total of 51 African men in South Africa, 56 British Africans, and 114 British Caucasians rated 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 48 publications
0
47
0
Order By: Relevance
“…However, these valued ideals are situated within a societal context that continually reinforces what acceptable standards of beauty are for Black and White women. As an example of shifting beauty ideals, recent work by Swami et al (2009) found that the ethnicity of a female silhouette figure influenced the breast, butt, and waist size that different groups of men found attractive. These findings suggest that race and cultural context play an important role in people's perceptions of ideal body types.…”
Section: Predictormentioning
confidence: 99%
“…However, these valued ideals are situated within a societal context that continually reinforces what acceptable standards of beauty are for Black and White women. As an example of shifting beauty ideals, recent work by Swami et al (2009) found that the ethnicity of a female silhouette figure influenced the breast, butt, and waist size that different groups of men found attractive. These findings suggest that race and cultural context play an important role in people's perceptions of ideal body types.…”
Section: Predictormentioning
confidence: 99%
“…European American men preferred profile images with a 0.7 WHR, while Hazda men preferred profile images with a 0.9 WHR (Marlowe et al, 2005). In an extension of Marlowe et al's study, Swami, Jones, Einon, and Furnham (2009) used British men who were classified as being European Caucasian or of African descent. They also used a sample of African men from Cape Town, South Africa.…”
Section: Ethnic Differencesmentioning
confidence: 99%
“…WHR also changes over women's lifetimes (Kirschner & Samojlik, 1991) and so indicates residual reproductive value (Marlowe, 1998). It has therefore been proposed that WHR serves as an important ornament display (Perilloux, Webster, & Gaulin, 2010;Singh, 1993) and much is now known about the effects of this (e.g., Dixson, Sagata, Linklater, & Dixson, 2010;Karremans, Frakenhuis, & Arons, 2010;Platek & Singh, 2010;Singh, Dixson, Jessop, Morgan, & Dixson, 2010;Swami, Jones, Einon, & Furnham, 2009;Vaidya et al, 2012).…”
Section: Introductionmentioning
confidence: 99%